Functionalization of Chitosan with 3,4,5-Trihydroxy Benzoic Acid Moiety for The Uptake of Chromium Species - Akhmad Sabarudin; Shoji Motomizu (The Journal of Pure and Applied Chemistry Research, 2013)
Chitosan-based chelating resin, the cross-linked chitosan functionalized with 3,4,5-trihydroxy benzoic acid moiety (CCTS-THBA resin), was newly synthesized and its adsorption behavior toward appropriate elements was investigated. At pH 5-9, the CCTS-THBA resin showed quantitative adsorption (87-91%) for Cr (VI), while only < 15% for Cr (III). The addition of cyclohexanediamine tetraacetic acid (CyDTA) to the samples resulted in a considerably increase of the adsorption of both chromium species. In this condition, Cr (III) is chelated with CyDTA to form anionic complexes at pH 3-5, which was then completely adsorbed on the resin by ion exchange mechanism. Similarly, the adsorption of Cr (VI) reached almost 100% in pH range of 3-6. The adsorption capacity of CCTS-THBA resin for Cr (VI) was 109 mg g-1.